A merganser at Auckland Islands, New Zealand - Williams, Murray (Wildfowl, 2012)
TThe last population of the merganser Mergus australis persisted at Auckland Islands in New Zealand’s Subantarctic until its extermination by specimen collectors in 1902. It is now represented by four duckling specimens, 23 skins of immatures and adults, three skeletons, and a partial cadaver stored in 11 museums. It was the smallest known Mergus, the males weighing c. 660 g and showing little plumage dimorphism from the smaller (c. 530 g) females. Only five published accounts report first-hand observations of its ecology, breeding or distribution. Most likely it occurred as yearround territorial pairs in the larger streams and along the coastal edge at the heads of Auckland Island’s eastern inlets and in Carnley Harbour and fed on both marine and fresh water foods. Its population probably never exceeded 20–30 pairs. The scant records suggest it had a typical summer breeding season. Although its keel area and wing skeleton were reduced relative to its sternum length it was well capable of flapping flight.